Confined space rescue: A proposed procedure to reduce the risks - Selman, J.; Spickett, Jeffery; Jansz, J.; Mullins, B. (Elsevier BV, 2019)
© 2018 Each year, workers are killed in incidents involving confined spaces. To minimise and control the risks so far as reasonably practicale, confined space work should be thoroughly considered and carefully planned before any entry. Unfortunately, when would-be rescuers attempt the rescue of fellow workers, multiple fatalities can result. Confined space rescue should always be a deliberate undertaking, planned prior to the confined space entry taking place, and conducted by trained personnel. This paper proposes a five step procedure to safely undertake confined space entry rescue, mindful of the hierarchy for protection (rescuers, bystanders, and casualties); and of the hierarchy of the level of confined space rescue (self-rescue, non-entry rescue, and entry rescue). The proposed confined space rescue procedure is a simplified and broad-based process for the preparation and conduct of a confined space rescue by on-site or in-house rescue teams, and is an adaptation of the procedures used by professional emergency services. The five step procedure is described by the acronym REALE. Step 1 is Reconnaissance of the rescue task. Step 2 is Elimination or reduction of hazards. Step 3 is Accessing the casualty, in which a minimal number of rescuers enter the confined space and make contact with the casualty. Step 4 is the provision of Life-saving first aid to the casualty. Step 5 is the Extrication of the casualty as required. The proposed procedure is suitable for adoption by rescue teams regardless of country or jurisdiction as it meets the requirements for all regulations and standards.